SPAG6 overexpression decreases the pro-apoptotic effect of daunorubicin in acute myeloid leukemia cells through the ROS/JNK MAPK axis in a GSTP1-dependent manner - Luo, Jie; Ding, Li; Pan, Shirui; Luo, Jing; Zhao, Haiqiu; Yin, Jiaxiu; Su, Rong; Zhang, Jiamin; Liu, Lin (Frontiers in Pharmacology, 2024)
As a malignant hematological disease, the incidence of acute myeloid leukemia (AML) has exhibited an upward trend in recent years. Nevertheless, certain limitations persist in the treatment of AML. Sperm-associated antigen 6 (SPAG6) has been implicated in the onset and progression of various human cancers, with its expression levels significantly elevated in AML. Consequently, we undertook a series of experiments to investigate the role and underlying mechanisms of SPAG6 in AML cell lines. Ultimately, our findings indicated that over-expression of SPAG6 promoted cell growth and decreased reactive oxygen species (ROS) and malondialdehyde levels. Furthermore, SPAG6 knockdown was found to diminish mitochondrial membrane potential and facilitate cell apoptosis. In vivo, SPAG6 could also promote tumor growth, suggesting that SPAG6 may serve as a pro-tumor factor. In addition, daunorubicin (DNR) may cause oxidative stress and initiate apoptosis, resulting in oxidative damage to AML cells. However, the overexpression of SPAG6 may attenuate the efficacy of DNR. This was due to SPAG6 promoted GSTP1 expression, thereby reducing ROS levels. Simultaneously, the elevation of GSTP1 and JNK complex may reduce the expression of p-JNK and inhibit the activation of JNK pathway, which might inhibit cell apoptosis. In conclusion, our experiments suggested that up-regulated SPAG6 might mitigate the pro-apoptotic effects of DNR through ROS/JNK MAPK axis in a GSTP1-dependent manner.